Biochemical Potential of Candida tropicalis in Enzymatic Degradation of Phenol: A Review - Butt1, Mahrukh; Nayab1, Durre; Hassan2, Waqas; Mehmood2, Zaffar; Farooq Hussain Munis1, Muhammad; Imran3, Muhammad; Javed Chaudhary1, Hassan (Asian Journal of Chemistry, 2014)
The pronounced and serious effects of phenol in the biosphere have attracted worldwide attention to keep its level below threshold in order to preserve the environment quality. The biochemical degradation through micro-organisms is cost effective among various methods to-date. The metabolic process of micro-organisms is governed by specific enzymes. Phenol is biochemically transformed into catechol followed by ring cleavage either at ortho or meta position incorporating end products in TCA cycle. The present article provides an overview of biochemical pathway adopted by Candida tropicalis to metabolize phenol through aerobic degradation.